Koncepcje innowacyjnych pomocy dydaktycznych Pracowni Mechatroniki Samochodowej i ich zastosowanie w kształceniu studentów kierunku mechatronika - Krupa, Krzysztof (Wydawnictwo Uniwersytetu Rzeszowskiego, 2016)
W artykule opisano zagadnienia realizowane w Pracowni Mechatroniki Samochodowej oraz aktualne jej wyposażenie. Ponadto przedstawiono szereg innowacyjnych pomocy dydaktycznych wykonanych przez studentów oraz perspektywy rozwoju Pracowni.

The article describes the issues carried out in the Laboratory of Mechatronics Motor and its current equipment. Also presented a series of innovative teaching aids made by students and prospects of development Laboratory.
The concepts of innovative teaching aids Mechatronics Laboratory of Automobile and their application in the education of students of mechatronics
Keywords: mechatronika; mechatronika samochodowa; pracownia mechatroniki samochodowej; innowacyjne środki dydaktyczne; mechatronics; automotive mechatronics; automotive mechatronics lab; innovative teaching aids